2022
DOI: 10.1002/aenm.202200001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ni/NiO@MoO3−x Composite Nanoarrays for High Current Density Hydrogen Evolution Reaction

Abstract: High current density hydrogen evolution reaction (HER) in alkaline water electrolysis plays crucial role in renewable and sustainable energy systems, while posing a great challenge to the highly‐efficient electrocatalysts. Here, the synthesis of Ni/NiO@MoO3−x composite nanoarrays is reported by a moderate reduction strategy, combining Ni/NiO nanoparticles (≈20 nm) with amorphous MoO3−x nanoarrays. The Ni/NiO@MoO3−x composite nanoarrays possess enhanced hydrophilicity, optimize reaction energy barriers, acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…Transition-metal-based electrocatalysts have shown great potential for overall water splitting over the past few years. Various oxides (MoO x ) [ 9 ], hydroxides (Ni(OH) 2 ) [ 10 , 11 ], sulfides (MoS 2 ) [ 12 ], selenides (MoSe 2 ) [ 13 ], nitrides (VN) [ 14 ], and carbides (MXene) [ 15 , 16 ] materials have been extensively reported as water splitting electrocatalysts. Among the aforementioned catalysts, transition metal phosphides (TMPs) possess a hydrogenase-like structure, and are regarded as promising nonprecious electrocatalysts for overall water splitting [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal-based electrocatalysts have shown great potential for overall water splitting over the past few years. Various oxides (MoO x ) [ 9 ], hydroxides (Ni(OH) 2 ) [ 10 , 11 ], sulfides (MoS 2 ) [ 12 ], selenides (MoSe 2 ) [ 13 ], nitrides (VN) [ 14 ], and carbides (MXene) [ 15 , 16 ] materials have been extensively reported as water splitting electrocatalysts. Among the aforementioned catalysts, transition metal phosphides (TMPs) possess a hydrogenase-like structure, and are regarded as promising nonprecious electrocatalysts for overall water splitting [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the increased water adsorption on Sn-Ru/C was demonstrated by the test of the contact angle (CA). As depicted in Figure b, the Sn-Ru/C and Ru/C show different hydrophilicities with water CAs of 145.8 and 132.0°, respectively, suggesting that Sn-Ru/C is much easier to contact with water than Ru/C . Water adsorption on the catalyst surface was also detected by Raman spectroscopic technology.…”
Section: Resultsmentioning
confidence: 99%
“…The final adsorption capacities of Ni–Co(OH)F, Co(OH)F@CoS 2 , Ni–Co(OH)F@NiCo 2 S 4 and NiCo 2 S 4 for H 2 were 4.0, 2.7, 0.98 and 0.54 mmol mg −1 , respectively. 11 The corresponding electrochemical curves further indicated that Ni–Co(OH)F has the most positive hydrogen adsorption peak with 0.438 V compared to NiCo 2 S 4 with 0.212 V, Ni–Co(OH)F@NiCo 2 S 4 with 0.242 V and Co(OH)F@CoS 2 with 0.333 V. As a more positive peak suggested the stronger adsorption for H species, 40 it can be summarized that the order of hydrogen adsorption ability was Ni–Co(OH)F > Co(OH)F@CoS 2 > Ni–Co(OH)F@NiCo 2 S 4 > NiCo 2 S 4 , which agrees well with the H 2 pulse chemical adsorption test results. In addition, the Ni 0 species appeared in the XPS spectrum of Ni–Co(OH)F@NiCo 2 S 4 core–shell nanorods possessing relatively weak adsorption for H species.…”
mentioning
confidence: 93%
“…In addition, the Ni 0 species appeared in the XPS spectrum of Ni–Co(OH)F@NiCo 2 S 4 core–shell nanorods possessing relatively weak adsorption for H species. 33,40 This may adjust the strong H adsorption behavior of Co in the Ni–Co(OH)F@NiCo 2 S 4 catalyst. 8,12,42 Therefore, the Ni–Co(OH)F@NiCo 2 S 4 core–shell nanorods show a moderate H adsorption behavior.…”
mentioning
confidence: 99%